Reimagining global health an introduction - Farmer, Paul, 1959- (California series in public anthropology, 2013)
"Bringing together the experience, perspective and expertise of Paul Farmer, Jim Yong Kim, and Arthur Kleinman, Reimagining Global Health provides an original, compelling introduction to the field of global health. Drawn from a Harvard course developed by their student Matthew Basilico, this work provides an accessible and engaging framework for the study of global health. Insisting on an approach that is historically deep and geographically broad, the authors underline the importance of a transdisciplinary approach, and offer a highly readable distillation of several historical and ethnographic perspectives of contemporary global health problems.The case studies presented throughout Reimagining Global Health bring together ethnographic, theoretical, and historical perspectives into a wholly new and exciting investigation of global health. The interdisciplinary approach outlined in this text should prove useful not only in schools of public health, nursing, and medicine, but also in undergraduate and graduate classes in anthropology, sociology, political economy, and history, among others"--Provided by publisher.